Influence of pre-existing hypertension on neuroendocrine and cardiovascular changes evoked by chronic stress in female rats - Vieira, Jonas O. [UNESP] (2018)
This study investigated neuroendocrine, autonomic, and cardiovascular changes evoked by daily exposure to the same type of stressor (homotypic) or different aversive stressor stimuli (heterotypic) in 60-days-old female normotensive Wistar rats and female spontaneously hypertensive rats (SHR). Both strains of rats were exposed for 10 consecutive days to either the homotypic stressor repeated restraint stress (RRS) or the heterotypic stressor chronic unpredictable stress (CUS). As expected, SHR had higher baseline blood pressure values and impaired baroreflex activity in relation to normotensive animals. Besides, SHR presented higher plasma corticosterone levels and decreased thymus weight. Both RRS and CUS increased baseline plasma corticosterone concentration and decreased body weight gain in both normotensive and SHR rats. In addition, both stress protocols caused hypertrophy of adrenal glands in normotensive rats. Regarding the cardiovascular effects, RRS increased basal heart rate in both rat strains, which was mediated by an increase in sympathetic tone to the heart. Besides, RRS increased baroreflex-mediated tachycardia in SHR animals, while CUS increased cardiac parasympathetic activity and pacemaker activity in normotensive rats. Taken together, these results indicate a stress type-specific effect, as identified by a vulnerability of both strains to the deleterious cardiovascular effects evoked by the homotypic stressor and a resilience to the impact of the heterotypic stressor. Vulnerability of hypertensive rats was evidenced by the absence of CUS-evoked adaptive cardiovascular responses and an increase of baroreflex tachycardia in SHR animals subjected to RRS. The somatic and HPA axis changes were overall independent of the chronic stress regimen and pre-existing hypertension.